Ion Transfer Voltammetry with an Electrochemical Pen - Podrażka, M.; Witkowska Nery, E.; Henares, Terence G.; Jönsson-Niedziółka, M.; Arrigan, Damien (AMER CHEMICAL SOC, 2020)
We present a new electrochemical system that combines paper-based sensing and ion-transfer voltammetry, bringing the latter a step closer toward point-of-care applications. Studies at the interface between two immiscible electrolyte solutions (ITIES) are often performed to detect redox-inactive species; unfortunately, due to the inherent instability of the interface, it is rather poorly explored outside specialized laboratories. Here, we address this limitation by combining a pen-like device containing the gelled organic phase with a paper-supported aqueous phase. This combination makes the system more user-friendly, potentially low-cost, and easy to assemble. We show the applicability of the new cell to analyze both simple and ionophore-facilitated transfer of ions and proteins, preconcentration of species, and analysis of mixtures through combination with paper chromatography. The native ion content of the paper also enabled measurements without added electrolytes. Those studies could broaden the scope for the application of the label-free electrochemical detection of nonredox-active species at points-of-need.